Ancient Judaism: New Visions and Views, Michael E. Stone : book review - Kotzé, Gideon R. (Old Testament essays, 2013)
In this book, Michael E. Stone examines several issues relevant to the study of Second Temple Judaism. It consists of seven chapters, an extensive and helpful bibliography and two indices (subjects and names, as well as ancient sources). In each of the chapters of the book, Stone discusses a different topic concerning our knowledge of Second Temple Judaism and some of the many sources of such knowledge, especially the Dead Sea scrolls, Apocryphal and Pseudepigraphical literature.